Effect of Staphyloxanthin on Biophysical Properties of Membrane Models: A Spectroscopy Study (2023)
ABSTRACT: Staphylococcus aureus (S. aureus) is a Gram-positive bacteria considered one of the most frequent pathogens in hospitals. 1 One of the most interesting features of S. aureus is the synthesis of lipids as a response to external factors. 2 Recently, staphyloxanthin (STX) production has been associated with bacteria pathogenicity since it is related to a higher tolerance to oxidative stress and presumably it plays a role in regulating membrane properties. 3, 4 In this study was evaluated the effect of increasing concentrations of STX on the thermotropic properties of cell membrane models of S. aureus. Infrared spectroscopy and fluorescence spectroscopy were used to evaluate the effect on system phase-transition temperature (Tm), and the changes in fluidity, respectively